The causes of persistent inflation in Nigeria - Victor O. Asekunowo (CBN Journal of Applied Statistics, 2016)
This study sought to identify the traditional and institutional inflation variables responsible for inflation phenomenon and the magnitude of the contribution of the identified variables to the rise in general price level. Secondary data on key macroeconomic variables in the economy from 1974 to 2013 were used. The data collected were analysed using the Autoregressive Distributed Lag (ARDL) bounds test. The results showed that there existed a longrun co-movement among the variables. Also, the ordinary least squares estimate showed that Real Effective Exchange Rate, Lagged Consumer Price Index, Real Broad Money and Real Profits were statistically significant in influencing Consumer Price Index. The short-run relationship shows that 60% of disequilibrium errors from the previous year's shock converge back to the long-run equilibrium in the current year. The study therefore concluded that inflation in Nigeria, during the studied period, was driven by the pass-through of import prices to domestic prices via markup pricing by firms. This was aided by domestic inflation persistence. It is therefore recommended that domestically produced products of good quality and adequate quantity must be substituted for imported ones and a monetary policy stance that does not easily deviate from the set monetary target should be adopted by the Nigerian monetary authorities if persistent inflation is to be curbed in the country.
Keywords: E30; E31; E50; E58; 330; Inflation; Real Exchange Rate Shocks; Pass-Through; Real Profits; Real Broad Money Supply; Inflation Persistence; Nigeria